1954
DOI: 10.1136/bmj.1.4865.792
|View full text |Cite
|
Sign up to set email alerts
|

Death from Hypersensitivity due to Phenylbutazone

Abstract: PHENYLBUTAZONE AND URIC ACID METABOLISM BEDI late from plasma uric acid readings before and after treatment the total loss of body uric acid and to correlate this calculation with the actual excess observed in the urine. Such a calculation is shown in Table VI. Case 4 is excluded, as measurements of actual body weight were not taken.Where more than one estimation of circulating uric acid was made before treatment the mean has been taken. Such calculations require certain assumptions which need not be discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1954
1954
1985
1985

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 9 publications
(2 reference statements)
1
5
0
Order By: Relevance
“…Bourne (1953) reported three patients in whom the lesion appeared obstructive, and\in another-not clinically jaundiced-granulomatous lesions were found in the portal tracts (O'Brien and Storey, 1954). In our patient the hepatitis appears to have been definitely toxic in nature.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Bourne (1953) reported three patients in whom the lesion appeared obstructive, and\in another-not clinically jaundiced-granulomatous lesions were found in the portal tracts (O'Brien and Storey, 1954). In our patient the hepatitis appears to have been definitely toxic in nature.…”
Section: Discussionsupporting
confidence: 48%
“…The involvement of so many different viscera in our patient suggests a hypersensitivity reaction. That such reactions occur in patients receiving phenylbutazone is made extremely probable by the microscopy findings in two fatal cases (Nathan et al, 1953;O'Brien and Storey, 1954). In both patients there were multiple and widespread vascular lesions.…”
Section: Discussionmentioning
confidence: 97%
“…The initial lesion is that in the respiratory tract, a granulomatous inflammation spreading from the mucosa, but there is little doubt that subsequent thrombosis of small vessels contributes to the development of the large necrotic areas in nares, glottis, and lung. The widespread granulomata resemble those found in experimental serum sickness (Rich, 1942), "allergic granulomatosis " (Churg and Strauss, 1951), and many cases of fatal drug sensitivity (Waugh, 1952;O'Brien and Storey, 1954;Rasmussen, 1955;and others). The necrotizing vascular lesions are morphologically similar to those in polyarteritis nodosa of the " microscopic " variety (Davson et al, 1948), "hypersensitivity angiitis" (Zeek, 1952(Zeek, , 1953, and experimental hypersensitivity (Rich and Gregory, 1943;McKeown, 1947;Crawford and Nassim, 1951;Germuth et al, 1955;and others).…”
Section: 1958mentioning
confidence: 76%
“…Effects were seen particularly in the leucocytes and liver (Steinberg et al, 1953 ;Engleman et al, 1954), and fatal cases of generalized visceral involvement were found (O'Brien and Storey, 1954;MacCarthy and Jackson, 1955;Hodge and Lawrence, 1957)., In view of this, the drug was reintroduced at a lower dosage, 200 mg. daily.…”
Section: Discussionmentioning
confidence: 99%